Four-Level Anterior Cervical Discectomy and Fusion for Cervical Spondylotic Myelopathy. (December 2016) - Wang, Shan-Jin; Ma, Bin; Huang, Yu-Feng; Pan, Fu-Min; Zhao, Wei-Dong; Wu, De-Sheng
Purpose: To review the outcome of 32 consecutive patients who underwent 4-level anterior cervical discectomy and fusion (ACDF) with cages and plates and were followed up for at least 5 years. Methods: Records of 19 men and 13 women aged 48 to 69 years who underwent 4-level ACDF with cages and plates for myelopathy (n=11) or myeloradiculopathy (n=21) at C3 to C7 by a single surgeon and were followed up for a minimum of 5 years were reviewed. Clinical outcome was assessed using the visual analogue scale (VAS), Neck Disability Index (NDI), and modified Japanese Orthopaedic Association (JOA) score for pain or myelopathic symptoms. Radiographic evaluation included fusion rate, range of motion, cervical lordosis (C2-to-C7 Cobb angle), and disc height. Results: The mean follow-up was 66 months. All patients had good recovery of muscle strength and resolution of limb sensory disturbance, except for 4 who still had some numbness. The mean VAS for neck and arm pain improved from 14.2 to 6.84 (p=0.012); the mean NDI improved from 31.62 to 12.17 (p<0.01); and the mean JOA score improved from 10.1 to 13.9 (p=0.027). The mean percentage of recovery was 62.9. The mean Cobb angle improved from 10.24° to 1.28° (p=0.019); the mean disc height improved from 4.12 to 6.58 mm (p<0.01). 30 (94%) patients achieved solid fusion. Conclusion: Multilevel ACDF using PEEK cages and plates is safe and effective for multilevel cervical spondylotic myelopathy and achieves satisfactory mid-term outcome.